Autophagy- and MMP-2/9-mediated Reduction and Redistribution of ZO-1 Contribute to Hyperglycemia-increased Blood–Brain Barrier Permeability During Early Reperfusion in Stroke. (1st May 2018) - Zhang, Shuai; An, Qier; Wang, Tianfu; Gao, Shuping; Zhou, Guangqian
Highlights: High glucose causes blood–brain barrier disruption in the early reperfusion of stroke. MMP-2/9-mediated extracellular ZO-1 degradation. Caveolin-1-mediated intracellular translocation of ZO-1. Autophagy-lysosome-mediated ZO-1 degradation. Abstract: Post-stroke hyperglycemia during early reperfusion increases blood–brain barrier (BBB) permeability and subsequently aggravates brain injury and clinical prognosis. The decreased level of tight junction proteins (TJPs) has been reported but the underlying mechanism remains largely elusive. Herein we designed to investigate the detailed molecular events in brain microvascular endothelial cells (BMECs) ex and in vivo . After oxygen–glucose deprivation (OGD) for 90 min and reperfusion with 8 or 16 mM glucose for 30 min, glucose at 16 mM caused significant decrease in the TJP expression and particularly ZO-1 redistribution from membrane to cytoplasm of BMECs. High glucose also markedly promoted the secretion of MMP-2/9 and oxidative/nitrosative stress, enhanced autophagy and increased the Caveolin-1 and LAMP-2 expression. Moreover, in vivo experiments demonstrated that rapamycin-enhanced autophagy further caused ZO-1 reduction and the increased BBB permeability. Therefore, high-glucose exposure in the early reperfusion causes the BBB disruption, with MMP-2/9-mediated extracellular degradation, caveolin-1-mediated intracellular translocation and autophagy-lysosome-mediated degradation of ZO-1 protein all together involved in the process. The role of MMP-2/-9 and autophagy in the modulation of paracellular permeability was confirmed by pharmacological inhibition. Therefore, our findings may provide new insights into targeting ZO-1 regulation for the purpose of significantly improving the clinical prognosis of ischemic stroke.